Relationship of Lipids and Lipid-Lowering Medications With Cognitive Function: The Multi-Ethnic Study of Atherosclerosis. Issue 4 (19th October 2017) - Ong, Kwok Leung; Morris, Margaret J; McClelland, Robyn L; Hughes, Timothy M; Maniam, Jayanthi; Fitzpatrick, Annette L; Martin, Seth S; Luchsinger, José A; Rapp, Stephen R; Hayden, Kathleen M; Sandfort, Veit; Allison, Matthew A; et al.
Abstract: Studies on the relationship of cholesterol concentrations and lipid-lowering medications with dementia risk have yielded inconsistent findings. Therefore, we investigated the association of lipid concentrations and lipid-lowering medications with cognitive function in the Multi-Ethnic Study of Atherosclerosis across 3 different cognitive domains assessed by means of the Cognitive Abilities Screening Instrument (CASI; version 2), the Digit Symbol Coding (DSC) Test, and the Digit Span (DS) Test in 2010–2012. After adjustment for sociodemographic and confounding factors, including concentrations of other lipids and use of lipid-lowering medication, higher total cholesterol, low-density lipoprotein cholesterol, and non–high-density-lipoprotein cholesterol concentrations were modestly associated with higher DS Test scores. None of the lipid parameters were associated with CASI or DSC Test scores. Similarly, changes in lipid concentrations were not associated with any cognitive function test score. Using treatment effects model analysis and after adjusting for confounding factors, including lipid concentrations, the use of any lipid-lowering medication, especially statins, was associated with higher scores on the CASI and backward DS tests but not on the DSC and forward DS tests. Our study does not support a robust association between lipid concentrations and cognitive function or between the use of lipid-lowering medication, especially statins, and worse cognitive function.